Structural design and axial compression test of novel carbon-fiber-reinforced polymer truss supporting rear connection-ring. (April 2023) - Li, Shiping; Chen, Wujun; Chen, Longlong; Mi, Xiang; Zhang, Yibei
Abstract: Based on the "light-weight, heavy-load, and large-span" composite truss design goal for the load-bearing structures of large aircraft, the joint construction pattern, modular integration approach, unique connection method for rear connection-rings, and structural design of composite trusses are studied in detail; a novel carbon-fiber-reinforced polymer (CFRP) truss supporting rear connection-ring is proposed. Based on the force characteristics of different section positions and the advantages of different joint types, three different joint types have been adopted: plate-shell-integrated joint (only single-K and double-K patterns), aluminum alloy joints, and butt joints. This can help fully analyze the advantages of different joint types and achieve the optimal design of composite trusses. Each truss module can be designed separately based on the specific functional and usability requirements, which increases the design freedom of the composite truss, and gives the composite truss an aesthetic three-dimensional structure. Based on the unique construction characteristics of the truss ends, axial compression performance tests were carried out on the designed and fabricated 1:1 CFRP truss prototype, with a span of 18.5 m, using specific axial loading equipment. The research results show that the unique connection method of the rear connection-ring achieved uniform load transfer from the rear connection-ring to the truss; the CFRP truss prototype meets two design requirements (bearing capacity ≥ 55.0 kN, axial compression deformation <1/1500), and is particularly suitable for the rear connection-ring to transmit large loads effectively. The proposed novel CFRP truss supporting rear connection-ring has the advantages of efficient structure assemblage, high design freedom, and flexible construction, which meets the design requirements in terms of truss functionality and realizes the "large-span, heavy-load, and light-weight" structural design goal. Highlights: A novel carbon-fiber-reinforced polymer (CFRP) truss supporting rear connection-ring is proposed. The joint construction pattern, modular integration approach, unique connection method, and structural design were effectively verified. The axial compression behavior of the CFRP truss supporting rear connection-ring is systematically studied. Three different joints are adopted to leverage the performance advantages of each joint and optimize the overall performance of the composite truss.